Responsive Data Table Solution with New Scrolling Control Gesture for Better User Experience - Čegan, Lukáš (Springer, 2017)
According to available statistics, nowadays more user browse websites on mobile devices than on a desktop computer. This brings new challenges for web developers on how to deal with such a heterogeneous environment of devices. Today, several different solutions are on the market for building responsive data tables. However, these solutions have their limits in the event that the table contains a large number of records. In this paper a new solution is proposed based on a new scroll control gesture and elimination of superfluous loading records. The impacts of the proposed solution to the user experience were investigated through an experiment whose results are presented and discussed in this paper.
Responzivní webová tabulka s novým gestem ovládání posunu dat pro lepší uživatelskou zkušenost
Keywords: Data table; Responsive design; User experience